Effect of Brand Identity and Brand Image On Customer Loyalty Case Study In Daihatsu Car Consumer - Susetyo, Catur Rachmad; Nilowardono, Sengguruh; Wulandari, Ani (Quantitative Economics and Management Studies, 2020)
Daihatsu Motor Co., Ltd. is the oldest Japanese car company known for its small car products or more agreed. The number of Daihatsu car consumers is quite a lot, in making purchases. This study aims to analyze the effect of brand identity and brand image on customer loyalty. This type of research uses a quantitative approach. Data collection uses interviews, observation, and questionnaire distribution. Using the nonprobability method with a purposive sampling approach. The population of this research is Daihatsu car consumers with a sample of 60 respondents. The analytical method used is SPSS v.20. Based on the results of this study concluded that brand identity and brand image have a significant effect on customer loyalty.